A STUDY ON PERCEPTION OF SMALL SCALE ENTREPRENEURS TOWARDS ECONOMIC EMPOWERMENT IN THIRUVANANTHAPURAM DISTRICT - Vidya V; G Sreekanth (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the multifaceted perceptions of economic empowerment held by small-scale entrepreneurs within the unique socio-economic landscape of Kerala, India. Recognizing the significant role of small businesses in Kerala’s economy and their potential as catalysts for individual and community-level economic advancement, this research delves into how these entrepreneurs conceptualize and experience economic empowerment. Moving beyond purely financial metrics, the study explores the diverse dimensions of empowerment as perceived by this crucial segment, encompassing aspects such as financial independence, control over resources and decision-making, social recognition, contribution to well-being, and personal growth. Ultimately, this research contributes to a more comprehensive understanding of economic empowerment from the perspective of those actively engaged in small-scale entrepreneurship in Thiruvananthapuram district. The insights gained from this study hold significant implications for policymakers, support organizations, and practitioners seeking to promote sustainable economic growth and empower local communities through the strengthening of the small business sector in the state. By understanding the entrepreneurs’ own definitions and experiences of economic empowerment, interventions can be more effectively tailored to their needs and aspirations, fostering a more inclusive and equitable economic landscape in Thiruvananthapuram district, Kerala.